Full panorama images of 33 field plot centres during the expedition to Northwest Canada, summer 2022 - Stefan Kruse; Sarah Haupt; Luca Farkas (PANGAEA, 2025)
During an expedition to northwest Canada in summer 2022, full panoramic images of the sampled vegetation plots were captured for documentation purposes. The images were taken with a 360 camera (Samsung Gear 360) and from the centre 2-4 images recorded at the centre position of the vegetation plot standing at different positions. The images were stitched in the supplied software to 360x180 panorama images (7776x3888 pixels, raw images). These were aligned in Hugin Panorama Software (https://hugin.sourceforge.io/) and humans or other artificial objects masked. The final panorama was blended and gaps or human shadow errors healed with GIMP resynthesizer plugin (https://github.com/bootchk/resynthesizer) and exported into one image with 7776x3888 pixels.